2016
DOI: 10.1002/glia.23010
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 receptor inhibits postnatal neurogenesis and sustains astrogliogenesis from the subventricular zone

Abstract: We previously demonstrated that activation of ATP P2X receptors during oxygen and glucose deprivation inhibits neuroblast migration and in vitro neurogenesis from the subventricular zone (SVZ). Here, we have studied the effects of adenosine, the natural end-product of ATP hydrolysis, in modulating neurogenesis and gliogenesis from the SVZ. We provide immunochemical, molecular and pharmacological evidence that adenosine via A1 receptors reduces neuronal differentiation of neurosphere cultures generated from pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…Postnatal and adult NSCs could have different differentiation potentials, although a recent study in vitro reported a similar behaviour of postnatal (p7) and adult (p42)-derived NSCs [28]. Despite this consideration, we decided to use adult animals for the in vivo protocol as the main aim of our study was to examine the response of neurogenic niches to FTY720 after injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postnatal and adult NSCs could have different differentiation potentials, although a recent study in vitro reported a similar behaviour of postnatal (p7) and adult (p42)-derived NSCs [28]. Despite this consideration, we decided to use adult animals for the in vivo protocol as the main aim of our study was to examine the response of neurogenic niches to FTY720 after injury.…”
Section: Discussionmentioning
confidence: 99%
“…NSC cultures were prepared from 4 to 7-day-old Sprague-Dawley rat pups, as previously described [27, 28], with slight modifications. Briefly, the SVZ was isolated and minced with a McIlwain tissue chopper.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, these few studies only report the expression of A 1 Rs, A 2A Rs, A 2B Rs, and A 3 Rs in NSCs isolated from adult mice SVZ. [52][53][54] Expression in DG NSCs has not been shown yet.…”
Section: Adenosine Receptors In Postnatal Neurogenesismentioning
confidence: 93%
“…53,55 Of interest, a recent study evaluating adenosine actions on SVZ demonstrates that adenosine, through A 1 Rs, reduces neuronal differentiation, correlating with a downregulation of proneurogenic genes. 54 Regarding A 2A R-mediated modulation of postnatal neurogenesis, A 2A R activation has been shown to inhibit primary SVZ-derived neurosphere proliferation. 52 Oliveros et al observed that the pharmacological blockade of A 2A R promoted impulsive behavior, and that in these conditions there was a potentiation of neuroblast proliferation, and likely of adult neurogenesis, in the dorsal hippocampus.…”
Section: Adenosine Receptors In Postnatal Neurogenesismentioning
confidence: 99%
“…Toward the end of the neurogenic phase, at approximately gestation day 17 in the mouse embryo, neocortical radial glia undergo a transition from a neurogenic to a gliogenic mode (“gliogenic switch”) and acquire gliogenic competence (Benito‐Muñoz, Matute, & Cavaliere, ; Li et al, ; Paridaen & Huttner, 2014; Rowitch & Kriegstein, ). During this transition, neurogenic genes are repressed and progliogenic genes are derepressed or activated through a variety of mechanisms, thereby allowing NPCs to respond to intrinsic and extrinsic progliogenic signals leading to the activation of specific glial cell lineage differentiation programs, ultimately resulting in the generation of cortical astrocytes and oligodendrocytes (Bayraktar, Fuentealba, Alvarez‐Buylla, & Rowitch, ; Ge & Jia, ; Li et al, ; Molofsky & Deneen, ; Rowitch & Kriegstein, ).…”
Section: Introductionmentioning
confidence: 99%